2004
DOI: 10.1161/01.cir.0000146952.49223.11
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Exposure During Catheter Ablation of Atrial Fibrillation

Abstract: Background-The purpose of this study was to determine the radiation exposure during catheter ablation of atrial fibrillation (AF) using the pulmonary vein (PV) approach. Methods and Results-The study included 15 patients with AF and 5 patients each with atrial flutter and atrioventricular nodal reentrant tachycardia (AVNRT) who underwent fluoroscopically guided procedures on a biplane x-ray system operated at a low-frame pulsed fluoroscopy (7.5 frames per second). Radiation exposure was measured directly with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
132
2
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 205 publications
(144 citation statements)
references
References 23 publications
7
132
2
3
Order By: Relevance
“…It is important to note that testing of Navik 3D shows the system does not require fluoroscopy exposure beyond the standard of care to generate detailed 3D maps. In fact, the mean fluoroscopy time in our studies was comparable to or less than the existing fluoroscopy times reported for similar studies (11). Navik 3D is likely to reduce fluoroscopy time (and dose) from standard amounts owing to the following: the catheter is visible in 3D and 2D when using Navik 3D; therefore, the physician is provided with better orientation information and is likely to use less fluoro.…”
Section: Figure 5 Secondary Analysis Regression Plot For Dn Vs DC (supporting
confidence: 69%
“…It is important to note that testing of Navik 3D shows the system does not require fluoroscopy exposure beyond the standard of care to generate detailed 3D maps. In fact, the mean fluoroscopy time in our studies was comparable to or less than the existing fluoroscopy times reported for similar studies (11). Navik 3D is likely to reduce fluoroscopy time (and dose) from standard amounts owing to the following: the catheter is visible in 3D and 2D when using Navik 3D; therefore, the physician is provided with better orientation information and is likely to use less fluoro.…”
Section: Figure 5 Secondary Analysis Regression Plot For Dn Vs DC (supporting
confidence: 69%
“…1,1241,1242,1243,1244,1245,1246,1247 Fluoroscopy is required for most components of the procedure, including catheter placement, positioning a multielectrode catheter into the CS, double transseptal catheterization, PV angiography, and LA ablation. A survey of the writing group members reveals that two-thirds use single-plane fluoroscopy, whereas one-third employ biplane.…”
Section: Section 10: Complicationsmentioning
confidence: 99%
“…[5][6][7] Among these, the PLDs used in this study have been extensively used in clinical and health physics dosimetry because they are sensitive to x-rays with sufficient accuracy through a wide range (ϳ10 Gy to 500 Gy) of detection. Compared with TLDs, PLDs can readout repeatedly until they are annealed to reset to zero.…”
mentioning
confidence: 99%